PENANAMAN KARAKTER DISIPLIN PADA SISWA SEKOLAH DASAR - Nugroho, Agung (universitas Ahmad Dahlan, 2020)
Curriculum 2013 which is currently applied in elementary schools is full of the values of character education. One of the 18 character values, which is felt to be the most needed to be developed, is discipline. Without reducing the urgency of other character values, discipline becomes one of the most important character values possessed by students, especially in primary schools so that later good character values emerge. Teachers and their staff as the front guard as well as agents in shaping the character of students in the school environment, absolutely must understand how to instill the value of character education in order to realize the objectives of the 2013 Curriculum. This article tries to elaborate and analyze the importance of the discipline character values possessed by students as well as what efforts can be done in order to instill the value of these characters especially for students in elementary school.